Theosophy of Human Concept in Pangestu: Sufism Perspective - Bakri, Syamsul; Wahyudi, M. Agus (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2021)
The study of humans has so far been dominated by Western schools of thought. As shown by psychoanalytic theorists, behaviorists, and cognitive theorists. Meanwhile, studies on humans that are sourced from local thinkers do not seem to have been discussed much by scholars. As the human concept that developed in the Pangestu mysticism in Indonesia. This article aims to examine the human concept according to the Pangestu school in terms of the process of human creation, the purpose of human life, and the relationship (union) of man with God. This study uses a descriptive qualitative approach. The results showed that human creation was caused by courtship from God or what is called Tri Purusa. Meanwhile, the purpose of human life is union with God or it is called ittihad and hulul. This study concludes that the teachings about humans in the Pangestu school are identical to those in Islamic philosophy and mysticism.